Physicochemical characterization of palladium-, platinum-, silver-doped magnesia nanoparticles and in vitro cytotoxicity in A549 (lung) and HT29 (colon) cancer cell lines - Khlaif, Mohamed Qasim (2019)
Cancers are one of the main causes of death in the developed countries. Currently, there is ongoing search for innovative therapeutics and strategies to combat the disease. This study was conducted to prepare three noble metal complexes, namely, palladium-, platinum-, and silver-doped magnesia designated Pt/MgO, Pd/MgO, and Ag/MgO nanoparticles, respectively, and to determine their cytotoxic potentials. These nanoparticles were prepared by hydrothermal impregnation method followed by calcination. The chemical compositions, functional groups, and optical properties of these nanoparticles were determined using X-ray diffraction (XRD), thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), and Brunner-Emmett-Teller (BET) surface area measurements. The sizes, size distribution, and morphology of nanoparticles have been determined by zetasizer. Transmission (TEM) and scanning electron (SEM) microscopy were also used to determine their ultrastructure and estimate the size of the nanoparticles. The cytotoxicity of these nanoparticles against the human colon (HT29) and lung cancer (A549), and normal human colon (CCD-18Co) and lung (MRC-5) cell lines was evaluated using the (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The caspase-3, -8 and -9, activities, and Bax, Bcl-2 and p53 protein expressions were also determined in cancer cells treated with Pt/MgO, Pd/MgO, and AG/MgO nanoparticles.